Epidemiology and serotype distribution of Streptococcus pneumoniae carriage among influenza-like illness cases in metropolitan Vientiane, Lao PDR: a community-based cohort study - Sanchez Picot, Valentina; Keovichith, Inthalaphone; Paboriboune, Phimpha; Flaissier, Bruno; Saadatian-Elahi, Mitra; Rudge, James W. (Frontiers in Public Health, 2023)
Background: Data on the epidemiology of Streptococcus pneumoniae among influenza-like illness (ILI) cases, particularly in low- and middle-income countries are scarce. This study assessed the prevalence, risk factors and serotype distribution of S. pneumoniae carriage among ILI cases in metropolitan Vientiane, Lao People’s Democratic Republic. The 13-valent pneumococcal conjugate vaccine (PCV13) was introduced among infants in October 2013. Methods: Active ILI surveillance was conducted through weekly phone calls in an open community-based cohort study (April 2015-February 2019), involving 5,690 participants from 1,142 randomly selected households. Participants reporting ILI symptoms provided a nasopharyngeal swab and answered a questionnaire. S. pneumoniae and serotype pneumococcal-positive samples were screened by Multiplex PCR assays. Chi-squared tests and generalized linear mixed models were used to test for variables associated with pneumococcal positivity. Results: Among 1,621 ILI episodes, 269 (16.6%) tested positive for nasopharyngeal pneumococcal carriage, with the highest prevalence (55.4%) in children under 5 years. Pneumococcal carriage was significantly associated with concurrent detection of Hemophilus influenzae (adjusted odds ratio [aOR]: 6.57; 95% CI: 2.00-21.6) and exposure to household cigarette smoke (aOR: 1.58; 95%CI: 1.02-2.43). PCV13 serotypes accounted for 37.8% of all pneumococcal isolates. Detection of PCV13 serotypes among ILI cases aged under 5 years declined significantly between 2015/16 and 2018/19. Conclusions: Community-based surveillance of S. pneumoniae among ILI cases complement surveillance at healthcare facilities to provide a more complete picture of pneumococcal carriage. Our findings contribute also to the growing body of evidence on the effects of PCV13 introduction on circulating serotypes and their potential replacement.